Texts for Keeping Watch: The Hymns of the Night of Ephrem of Nisibis and the Book of Lamentation of Gregory of Narek - Siragan Arlen, Jesse (Viator, 2018)
Abstract Most surviving texts from late antique and medieval Christianity reveal a profound preoccupation with asceticism. Many authors viewed their literary work as an ascetic discipline in its own right, and some texts were composed specifically to be used in conjunction with the performance of an ascetic practice. This paper centers on two such texts, written in different languages, centuries, and ascetic contexts, but bearing the similarity that they were both written to be used while performing vigil or keeping watch. The first are hymns (madrāše) of the fourth-century Syriac author Ephrem of Nisibis (d. 373). Seven of these are preserved only in Armenian, and bear the superscript Գիշերոյ կցուրդ (Gišeroy kc‘urd,